2012
DOI: 10.17221/6013-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of resistance to quaternary ammonium compounds - the qac genes and their role: a review

Abstract: ABSTRACT:Although the qac genes are named after one of their main substrates (i.e., quaternary ammonium compounds), these genes also code for resistance to a broad spectrum of other cationic compounds such as intercalating dyes, diamidines and biguanides. The various Qac proteins are involved in relatively low specific effluxbased multidrug pumps and belong to a family of small multidrug resistance proteins. Even though the practical significance of qac-mediated resistance lies mainly in resistance to antisept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 72 publications
3
71
0
Order By: Relevance
“…A total bacterial resistance against QACs is unlikely due to their nonspecific action (Weber and Rutala 2006;Maillard 2007;Bragg et al 2014;Gerba 2015;Jaglic and Cervinkova 2012). Bacteria with a significant increase in MICs against QAACs, however, might still be susceptible to commonly applied concentrations of biocides.…”
Section: Effects Of Qaacs On the Soil Microbial Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…A total bacterial resistance against QACs is unlikely due to their nonspecific action (Weber and Rutala 2006;Maillard 2007;Bragg et al 2014;Gerba 2015;Jaglic and Cervinkova 2012). Bacteria with a significant increase in MICs against QAACs, however, might still be susceptible to commonly applied concentrations of biocides.…”
Section: Effects Of Qaacs On the Soil Microbial Communitymentioning
confidence: 99%
“…Various qac genes have been described, which are widely spread among clinical and environmental bacteria and code for energy-dependent efflux pumps targeting a wide range of more than 30 lipophilic cationic compounds from at least 12 different chemical classes (Jaglic and Cervinkova 2012). Furthermore, for qacC it was shown that it confers resistance to a number of b-lactam antibiotics (Fuentes et al 2005).…”
Section: Role Of Qaacs In the Selection Of Antibiotic Resistancementioning
confidence: 99%
“…The QAC-resistance genes are typically located among integrons in Gram-negative bacteria, while in S. aureus they are usually related to plasmids carrying antimicrobial-resistance genes (Jaglic and Cervinkova, 2012;Argudín et al, 2014). However, the presence of class 1 integrons in clinical MRSA isolates has been described (Xu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The dfrB4 gene was carried with intI1 (class 1 integron integrase/recombinase) and tnpA (transposase), which are indispensable for integration of mobile genetic elements (23). Moreover, multiple antibiotic, biocide, and metal resistance genes were identified: qacEΔ1 (biocide resistance [24,25]), sulI (sulfonamide resistance [26]), the mphR(A)/mphA/mrx gene cluster (macrolide/erythromycin resistance [27]), and chrA (chromate resistance [28,29]). The qacEΔ1 gene encodes a truncated and less-efficient cation efflux pump version of qacE (24).…”
mentioning
confidence: 99%